A Prospective Hospital Based Observational Study On Electrolyte Changes Following Phototherapy In Neonatal Hyperbilirubinemia - Reddy.N, Varsha; .J, Krishnappa (Journal of Neonatal Surgery, 2025)
Background: Neonatal hyperbilirubinemia (NH) is a common condition affecting a large proportion of term and preterm infants. Phototherapy is a widely used treatment modality; however, it may result in electrolyte disturbances such as hypocalcemia, hyponatremia, and hyperkalemia, which pose significant clinical concerns. Objectives: This study aimed to evaluate changes in serum calcium, sodium, and potassium levels in neonates undergoing phototherapy for unconjugated hyperbilirubinemia. Methods: A hospital-based prospective observational study was conducted at RL Jalappa Hospital, Kolar, from August 2023 to August 2024. A total of 193 neonates aged between 24 hours to 14 days receiving phototherapy were enrolled. Electrolyte levels were measured before and after phototherapy and analyzed using appropriate statistical methods. Results: Hypocalcemia was observed in 24% of neonates post-phototherapy, significantly more common in preterm and low birth weight infants (p<0.001). Hyponatremia was found in 3.5% of cases, with a higher prevalence in preterm and LBW neonates. Hyperkalemia occurred in 4.2% of neonates post-phototherapy, although no significant hypokalemia was detected. The duration of phototherapy and gestational age showed a statistically significant correlation with electrolyte disturbances. Conclusion: Phototherapy in neonates is associated with significant electrolyte imbalances, particularly hypocalcemia and hyponatremia, especially in preterm and low birth weight infants. Routine monitoring of electrolytes during phototherapy is recommended to prevent complications.